2006
DOI: 10.2337/diabetes.55.02.06.db05-1022
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor Blockade Improves β-Cell Function and Glucose Tolerance in a Mouse Model of Type 2 Diabetes

Abstract: We identified an angiotensin-generating system in pancreatic islets and found that exogenously administered angiotensin II, after binding to its receptors (angiotensin II type 1 receptor [AT1R]), inhibits insulin release in a manner associated with decreased islet blood flow and (pro)insulin biosynthesis. The present study tested the hypothesis that there is a change in AT1R expression in the pancreatic islets of the obesity-induced type 2 diabetes model, the db/db mouse, which enables endogenous levels of ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
161
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 47 publications
8
161
0
1
Order By: Relevance
“…Concurrently, we have demonstrated local RAS expression in pancreatic islets, which varies with glycaemic control [1] and is excessively expressed in a mouse model of type 2 diabetes [2]; angiotensin II type 1 receptor (AT 1 receptor) blockade improves islet function and glucose tolerance in hyperglycaemia [2]. Hyperglycaemia may be worsened through AT 1 receptor-induced uncoupling protein 2-driven oxidative stress, reducing islet beta cell mass and insulin secretion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, we have demonstrated local RAS expression in pancreatic islets, which varies with glycaemic control [1] and is excessively expressed in a mouse model of type 2 diabetes [2]; angiotensin II type 1 receptor (AT 1 receptor) blockade improves islet function and glucose tolerance in hyperglycaemia [2]. Hyperglycaemia may be worsened through AT 1 receptor-induced uncoupling protein 2-driven oxidative stress, reducing islet beta cell mass and insulin secretion [3].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other reports on isolated rat and human pancreatic islets show that angiotensin II impairs the first phase of glucose-stimulated insulin secretion [18][19][20]. Angiotensin II also impairs insulin biosynthesis and promotes β cell apoptosis [21]. Thus, despite its acute action to stimulate release of insulin, the long-term effects of angiotensin II on the pancreas promote the development of diabetes.…”
Section: Ras In the Endocrine Pancreasmentioning
confidence: 56%
“…In this way, b-cells are exposed to other cell-derived molecules that can affect the physiological regulation of glucose-induced insulin secretion. It was demonstrated that endothelial-derived molecules, like endothelin-1, thrombospondin-1, and laminins, among others, can improve b-cell function [45][46][47]. These data show the importance of soluble factors secreted by islet vicinity, suggesting that the addition of soluble factors can also interfere in cell differentiation.…”
mentioning
confidence: 94%